History based multi-node collaborative localisation in mobile wireless ad hoc networks. (2019) - Liu, Defang; Guo, Songtao; Chen, Wenyuan; Wang, Fei
In most existing localisation algorithms, increasing the density of anchor nodes is one of the main strategies to improve the localisation accuracy in dense ad hoc wireless networks. In this paper, based on the number of reference nodes, we propose a distributed localisation algorithm, i.e., history based multi-node collaborative localisation algorithm (HMCL), in sparse ad hoc wireless networks. In the proposed HMCL algorithm, we exploit a new motion model to filter the imprecise estimation based on the historical position information of nodes, which can improve the localisation accuracy. Moreover, we utilise different strategies to achieve the localisation of nodes with different priorities measured by the distance between neighbour nodes. We verify through experiment that the proposed algorithm provides higher localisation precision and less energy consumption. Besides, we also analyse the effect of the number of neighbour nodes, node density and moving speed of nodes on localisation precision.